Autoimmune pancytopenia following combination chemotherapy for chronic lymphocytic leukaemia. Issue 5 (27th April 2009) - MacCallum, S; Groves, M; Brass, D; Cunningham, J; Sales, M; Gelly, K; Tauro, S
Abstract : Autoimmune haemolysis or thrombocytopenia can complicate purine nucleoside monotherapy for chronic lymphocytic leukaemia (CLL), but Evans syndrome is rare. This is a report of the occurrence of pancytopenia secondary to a unique combination of red cell aplasia with autoimmune thrombocytopenia and neutropenia in a patient with CLL following treatment with fludarabine and cyclophosphamide. This case is unusual for the simultaneous targeting of three haemopoietic lineages by immune dysfunction following fludarabine and cyclophosphamide, which is a treatment regimen believed to reduce autoimmune haematological toxicity in CLL.